Evolução geológica pré-cambriana e aspectos da metalogênese do ouro do cráton São Luís e do Cinturão Gurupi, NE-Pará/ NW-Maranhão, Brasil - KLEIN, Evandro Luiz (Universidade Federal do Pará, 2017)
In the Gurupi region, located at the border between the Pará and Maranhão states in northern Brazil, igneous and metamorphic rocks crop out as part of the Parnaíba Structural Province. Early geochronological studies, based on the Rb-Sr and K-Ar methods have shown two geochronological domains. The rocks that crop out towards the Atlantic margin showed a Paleoproterozoic signature, around 2000 Ma, whereas the rocks that crop out towards the inner portions of the continent showed a Neoproterozoic signature, especially between 800 and 500 Ma. These domains have been then defined as the São Luís Craton and Gurupi Belt, respectively. Several lithostratigraphic propositions have been developed throughout more than two decades. However, these propositions always lack robust geochronological support. Geotectonic models discussed a one- or two-phase evolution for the Gurupi Belt, also lacking robust geochronological and isotopic data to consubstantiate the interpretations. Furthermore, among the several gold deposits that occur in both the cratonic and belt areas, only a few have geological and genetic information. These subjects are addressed in more or less depth by this thesis. New propositions for the regional lithostratigraphy and geological evolution have been achieved in this work by revaluating the available geological, geochemical, geochronological and isotopic dataset, as well as by adding new geochronological data on zircon (Pb-evaporation, U-Pb ID-TIMS, and LAM-ICP-MS) for most of the igneous and orthometamorphic rocks in the region. Whole rock Nd isotope data have also been obtained, allowing the discussion of crustal accretion and reworking. The results show a rather complex geological evolution with intensive and extensive crustal growth between 2.24-2.15 Ga and crustal reworking, involving melting, migmatization, metamorphism, and deformation around 2.10 Ga. The following results have been obtained for the São Luís Craton: Aurizona Group, metavolcano-sedimentary sequence, maximum age of 2241 Ma (juvenile) that possibly evolved until c.a. 2200 Ma; Tromaí Intrusive Suite, calc-alkaline, metaluminous tonalites of oceanic island arc, 2168 Ma (juvenile); Areal Granite, calc-alkaline, weakly peraluminous, 2150 Ma (mixing of juvenile and arc materials). In the Gurupi Belt, the following results have been obtained: Igarapé Grande Metatonalite, small and localized granoblastic tonalite, 2594 Ma; Itapeva Complex, weakly migmatized tonalitic orthogneiss, 2167 Ma (mostly juvenile); Chega Tudo Formation, metavolcano-sedimentary sequence (back-arc basin?), 2150-2160 Ma; Maria Suprema Granite, syntectonic, peraluminous muscovite-bearing granite, 2100 Ma (similar to other peraluminous granitoids in the Gurupi Belt). The Gurupi Group is tentatively placed in the Paleoproterozoic (>2160 Ma), but this must still be proved. The above data are interpreted on a plate tectonics basis, as follows. An oceanic basin is open at ca. 2260 Ma and is followed by the onset of subduction, formation of island arcs and voluminous calc-alkaline magmatism in oceanic settings, and concomitant reworking of the arcs between 2170-2150 Ma. This set of oceanic terranes has been accreted (soft-collision) onto an Archean continental margin to southwest (Archean part of the Amazonian Craton or a present day concealed cratonic nuclei). The collision provoked the metamorphism, deformation, and partial melting of the newly formed Paleoproterozoic crust and of part of the Archean bloc, or their erosive detritus, migmatization, and emplacement of peraluminous granitoids at 2100-2080 Ma. The region has been the locus of a second event in the Neoproterozoic. A continental rift developed in the bloc that was assembled in the Paleoproterozoic, as attested by the intrusion of a nepheline syenite (Boca Nova) at 732 Ma. Sedimentary rocks that filled this rift (Marajupema Formation) have detrital zircon crystals that show the youngest ages around 1100 Ma. The rift evolved probably to an oceanic basin, as suggested by the widespread occurrence of detrital zircons with ages around 550 Ma in small sedimentary basins that have been filled with immature sediments. The precise time of orogenesis climax that followed basin closure, with mass transport from SSW to NNE and accompanying metamorphism, is not yet constrained. Equivocal geochronological information point to 650-520 Ma (zircon of the nepheline syenite, Rb-Sr and KAr ages in minerals). The metallogeny of selected gold deposits occurring in both the São Luís Craton and the Gurupi Belt is addressed using varied information, such as geology, chlorite chemistry, fluid inclusion geochemistry, and stable (O, H, C, S) and radiogenic (Pb) isotopes. Structural and textural relationships, and Pb isotope data indicate a post metamorphic peak and late- to posttectonic timing for the gold mineralization with respect to the Paleoproterozoic events (post 2080 Ma). At a regional scale, the deposits show a similar signature characterized by formation temperatures between 280° and 380°C; pressures of 2-3 kbars; low-salinity (5 mass % NaCl equiv), reduced and moderately dense aqueous-carbonic (CO2 <20 mol%, traces of CH4 and N2), showing strong evidence for phase separation. Stable isotope studies suggest distinct sources for fluids and solutes. The carbonate, graphite, and fluid inclusion carbon comes from two sources: a depleted organic source, and an unknown source that may be magmatic, metamorphic or mantlederived (or both). Sulfide sulfur derived directly from magmas or from the dissolution of magmatic sulfides. Combined oxygen and hydrogen isotopes attest a metamorphic source for the fluids. Therefore, dehydration and decarbonization reactions during the metamorphism of the Paleoproterozoic metavolcano-sedimentary sequences appear to have produced the mineralizing fluids. Gold was transported as a reduced sulfur complex, such as the Au(HS)2 - and precipitated in response to the breakdown of this complex due to phase separation and fluid-rock interactions. The geological and genetic constraints are consistent with the orogenic gold model, found in metamorphic belts of all ages. As a whole the results of this study have implications for the understanding of the Paleoproterozoic and Neoproterozoic orogenies that built up the South American Platform and for the assembly and break-up of the Atlantica, Rodinia, and West-Gondwana supercontinents. The geological scenario outlined here for the Paleoproterozoic shows good correlations with those found especially in the southeastern Guyana Shield and in the southern portion of the West- African Craton. For the Neoproterozoic, the available information is still insufficient to draw major correlations.